2010
DOI: 10.1002/aur.155
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced connectivity between visual cortex and other regions of the brain in autism: a REM sleep EEG coherence study

Abstract: Functional interregional neural coupling was measured as EEG coherence during REM sleep, a state of endogenous cortical activation, in 9 adult autistic individuals (21.1±4.0 years) and 13 typically developed controls (21.5±4.3 years) monitored for two consecutive nights in a sleep laboratory. Spectral analysis was performed on 60 s of artefact-free EEG samples distributed equally throughout the first four REM sleep periods of the second night. EEG coherence was calculated for six frequency bands (delta, theta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 24 publications
5
59
0
Order By: Relevance
“…In addition to the results of EEG coherence during REM sleep of Achermann and Borbely [2,3] (see Section 1), Leveille et al demonstrated that although intra-hemispheric EEG coherence (up to beta band) during REM sleep is altered in autism, inter-hemispheric coherence did not change [21]. Inter-hemispheric communication during REM sleep was also assessed by means of paired-pulse transcranial magnetic stimulation [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the results of EEG coherence during REM sleep of Achermann and Borbely [2,3] (see Section 1), Leveille et al demonstrated that although intra-hemispheric EEG coherence (up to beta band) during REM sleep is altered in autism, inter-hemispheric coherence did not change [21]. Inter-hemispheric communication during REM sleep was also assessed by means of paired-pulse transcranial magnetic stimulation [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…In one example, enhanced functional connectivity in autism was reported between the thalamus, the perceptual gateway of the brain, and several areas throughout the cortex (Mizuno et al, 2006). Increased task-independent functional connectivity among autistics was also reported in frontal-frontal and occipital-occipital pairs of areas (Noonan et al, 2009), and superior EEG coherence between the visual cortex and other regions of the brain was observed in autism during REM sleep (Léveillé et al, 2010). It is therefore at least plausible that, far from an overall functional underconnectivity between sensory regions and other areas of the brain, perception in autism may be driving brain network activity under some physiological and experimental conditions.…”
Section: Increased Connectivity Within Perceptual Areas and Between Pmentioning
confidence: 98%
“…As in the imaging reports, the resulting evidence is conflicting and inconsistent. Twenty-one studies in the last decade have been published; 11 evaluated resting state (Murias et al 2007;Coben et al 2008;Barttfeld et al 2011;Bosl et al 2011;Duffy and Als 2012;Mathewson et al 2012;Sheikhani et al 2012;Leveille and Hannagan 2013;Peters et al 2013;Machado et al 2015), eight were task related (Isler et al 2010;Lazarev et al 2010;Catarino et al 2013;Garcia Dominguez et al 2013;Carson et al 2014;Orekhova et al 2014;Righi et al 2014;Lazarev et al 2015;Machado et al 2015); one obtained during non-rapid eye movement (NREM) sleep (Lazar et al 2010) and one obtained during rapid eye movement (REM) sleep (Leveille et al 2010). It is not possible to directly compare these studies as the acquisition paradigm, the age of the subjects, Figure 3.…”
Section: Aberrant Connectivity In Autismmentioning
confidence: 99%